Biodigestão e co-digestão anaeróbias de cama de frangos com água residuária de suinocultura - Vicente Junior, Donizete Jose (2012)
Brazil has great potential in food production, although the large scale production of grains and animal protein has increased waste generation. This justifies the study of recycling practices, such as biodigestion and anaerobic co-digestion of wastewater, excreta and solid waste from farms and processing products since the processing of potential polluting waste into biofertilizers and biogas has contributed to effective sanitation and added value to the final product. The studied wastes were reused poultry litter from six, seven and eight lots and sieved swine wastewater (SWW), from piglet production unit. Two trials were carried out: the first one aimed at verifying which system, biodigestion or anaerobic co-digestion, has recorded the greatest potential for biogas production. With those results from the first trial, the second one could be started to determine the best hydraulic retention time (40 or 55 days), according to the following evaluated parameters: pH, electrical conductivity (EC), reduction of both total solids (TS) and volatile solids (VS), reduction of chemical oxygen demand (COD), N, P, K, Ca, Mg, Zn, Cu, Fe, Mn and Na contents, both in influent and effluent as well as the potential biogas production and analysis of total and thermo-tolerant coliforms. The results have shown higher biogas production (p <0.05) in treatments that used anaerobic co-digestion with SWW (0.179, 0.158 and 0.117 m3 kg added TS) for poultry litter with six, seven and eight lots, respectively. In this trial, there was no interaction among factors (poultry litter and used wastewater) or differences among treatments for COD decrease. For the second test, when hydraulic retention times were compared, the biogas production was statistically higher (p <0.05) in 55 day (0.04, 0.05 and 0.03 m3/kg TS added), respectively for poultry litter with six, seven and eight lots. According to COD decrease, the largest decreases (p <0.05) were observed at 55 days (45.83, 67.49 and 29.45%), respectively, for the poultry litter with six, seven and eight lots. There was no total or thermo-tolerant coliform in biofertilizer, in both trials. According to the chemical composition of biofertilizers, there was higher concentration of nutrients in effluent when compared to the influent due to carbon losses in biogas for both trials. In the first trial, the Mg levels remained the same in both biofertilizers from co-digestion as in anaerobic digestion. For other nutrients, the biofertilizer from co-digestion of the increases ranged from 20.2% for Ca up to 92% for N. In the first trial, both processes were compared and there was an increase on nutrients concentration in co-digestion biofertilizers and the increases ranged from 20.2% for Ca up to 92% for N. For micronutrients, the variation was from 55.2% up to 904.7% in Cu. Thus, it was concluded that the anaerobic co-digestion of sieved swine wastewater and poultry litter with six, seven or eight lots plus a 55 day hydraulic retention time is the best option for recycling energy and nutrients, although it has resulted in greater concentration of Cu and Zn in biofertilizer